Politics Without Television: The Bahujan Samaj Party and the Dalit Counter-Public Sphere - Loynd, Maxine (Television in India: Satellites, Politics and Cultural Change, 2008)
The place of the media in an effective liberal democracy is generally seen assacrosanct. The media play an important role in the collection and dissemination of information and provide an avenue for keeping politiciansaccountable to their constituents.Mindful of the impact themedia can have onthe fortunes of a political party, and the careers of individuals within it, mostpoliticians in liberal democracies tend to tread carefully in terms of how theymanage their relationship with the media. Politicians hire public relations andmedia advisors, and seek media training in order to learn how to ‘use’ themedia to further their political aims. In the main, the approach of India’spolitical parties to media relations has become remarkably similar. However, an exception appears when we examine the relationship of theBahujan Samaj Party (BSP), and its leader Mayawati, with the media in bothits mainstream forms – print and television. Despite early attempts to engagewith the media, by the late 1990s the BSP was running election campaignswith a media strategy of almost complete disengagement. This has not led topoor electoral results for the party. In fact, the party has been in power in thenorth Indian state of Uttar Pradesh (UP) on a number of occasions: in 1995,1997 and 2002, either in coalition or as a minority government. Upon winning minority government in the 2002 election, a journalist declared that ‘Inan age of television and information technology, Mayawati is a politician whodefies all conventional standards and norms . . . [and] despises giving interviews . . . ’(Bhushan, 2002: 18). In May 2007 the BSP won the UP state election outright to take power as the first majority government that UP hasseen for 15 years. Again this election was won while largely ignoring main-stream newspapers and television, with Mayawati even taunting journalistsafter the win, ‘I know you were upset I did not meet you during the campaign but I noticed that you had already run ahead with your conclusions, so Ithought why disturb you?’ (Gopinath, 2007).
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Inde (corpus analysé); _Nettoyé

Unpacking Multiculturalism and Islam in Malaysia: State–Corporate Television Celebrations of Bangsa Malaysia - Khattab, Umi (Television Histories in Asia: Issues and Contexts, 2015)
This chapter presents a critical analysis of media and change in postcolonial Malaysia, a South-East Asian nation of 29  million multicultural people, with a focus on the role of television in the nation’s transformation following independence from British rule in 1957. Despite having inherited the basic democratic institutions of the British political tradition, Malaysia continues to debate the transition from soft authoritarianism to democracy (Means 1996 :  103). Since 1957, Malaysia has been led by a single political party, the Barisan Nasional (BN). While the BN is a coalition of three major ethnic-based political groups, the United Malays National Organisation (UMNO), Malaysian Chinese Association (MCA) and the Malaysian Indian Congress (MIC), it is, in effect, a symbol of Malay-Muslim supremacy (Ketuanan Melayu). UMNO, the dominant group within the party, has, since its formation, aspired to uphold Malay culture as national culture and Islam as the offi cial religion for the country. From the fi rst general elections in 1959 until the 2008 general elections, the BN held two-thirds of the 222 seats in the Dewan Rakyat (House of Representatives). Malaysian media scholar Karthigesu ( 1987 , 1994 ) contends this was largely due to the role of public television, which was launched and promoted by government itself, broadcasting in its colonial service model. In fact, the arrival of state television in 1963 coincided with the formation of the Federation of Malaysia (Moten and Mokhtar 2013 ). In this chapter I argue that television has been pivotal in shaping and transforming the political and cultural landscape of Malaysia as the medium evolved from a strictly national to a loosely global and then fluidly trans-local orientation. While television fi rst enabled the BN to hold its two-thirds majority and build the nation premised on Malay supremacy policies, it subsequently played a part in weakening the BN’s grip over the multiethnic electorate as the UMNO Ketuanan Melayu ideology, layered deep beneath the powdered face of television, surfaced in the digital media era.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Malaisie (corpus analysé); _Nettoyé

Battling Angels and Golden Orange Blossoms: Thai Television and/as the Popular Public Sphere - Farmer, Brett (Television Histories in Asia: Issues and Contexts, 2015)
On 19 September 2006, the fi rst indication many people in Thailand received that the country was undergoing another military coup d’ é tat, the eighteenth such putsch since 1932, was when the nation’s six free-to-air television networks suddenly suspended regular programming and, channel by channel, started to broadcast a generic mix of royal news and light entertainment (Connors and Hewison 2008). Final confi rmation came again via television later that evening in the form of an offi cial announcement, broadcast at regular intervals across all stations from a central feed, in which the armed commanders in chief behind the coup – the awkwardly titled ‘Administrative Reform Group under the Democratic System with the King as the Head of State’ – explained apologetically that they had temporarily taken control of the nation’s airwaves, as indeed of the nation, exhorting viewers to remain calm and reassuring them that normalcy would soon be restored, at which point broadcasting reverted to the same steady flow of innocuous entertainment programming. For all its exceptional gravity, the 2006 coup’s strategic blend of direct state interventionist control of broadcasting combined with a more indirect use of escapist entertainment as populist pacifi er is arguably a structural characteristic of Thai television history writ large.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Thaïlande (corpus analysé); _Nettoyé

Globalizing Lifestyles? Makeover Television in Singapore - Lewis, Tania (The Politics of Reality Television: Global Perspectives, 2010)
The past decade has seen an explosion of lifestyle makeover television shows with audiences being urged to “renovate” everything from their homes, bodies, and children to their pets, a process that has seen the emergence of an army of lifestyle gurus on television advising us on what not to eat and what not to wear. While critical academic attention has largely focused on blockbuster reality television formats like Big Brother and Survivor, more recently a growing body of scholarship has started to focus on the “lifestyle turn” on television and the rise of the makeover format. To date much of the work on makeover television has focused on its role in the US and UK. However, in the past couple of years the lifestyle makeover show has become an increasingly global phenomenon with audiences around the world embracing everything from home renovation to plastic surgery makeover shows. This essay is concerned with examining the implications of the global dissemination of such modes of programming, associated as they are with ideologies of neoliberal individualism, self-surveillance and self-promotion, and with a strongly consumption-oriented aesthetic. It emerges out of a pilot study I have been conducting with Dr Fran Martin at the University of Melbourne as a preliminary step in a larger transnational comparative study of lifestyle programming in Asia in which we seek to examine the role of lifestyle television in both shaping and reﬂecting broader shifts in social and cultural identity accompanying the rise of consumer-based modes of modernity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Singapour (corpus analysé); _Nettoyé

Asia: New Growth Areas - Keane, Michael (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
The previous chapter introduced in broad brushstrokes the issues at stake in this study, beginning with a critique of globalization and moving on to sketch in ﬁner detail national television systems, the role of local content, and the economic importance of formats. The chapter concluded with a brief overview of the vagaries of copyright law as it applies to formats. Here, we initiate a discussion of Asian television systems beginning with a much different perspective on the ramiﬁcations of cultural borrowing. In this context we note that the format business straddles the divide between creative endeavour and innovation on the one hand, and slavish imitation on the other. This polarization manifests in widespread misunderstanding of the goals of format producers and distributors, and the role that formats play in the shaping of television schedules. We need therefore to ﬂesh out the in-between issues. These are primarily concerned with the relationship between the format and its localization, television consumption within ‘cultural continents’, and changes in media systems. Taking this further we note the relationship between production and reception within Asia, the growth of television industries in the region and the relationship between formatting and new media distribution platforms that use interactive technologies allowing viewers to feedback responses. This exercise enables us to identify an alternative list of conceptual tools to those championed by political economy scholars.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Television in Post-Reform Vietnam: Nation, Media, Market - Nguyen-Thu, Giang (Routledge, 2018)
This book explores Vietnamese popular television in the post-Reform era, that is, from 1986, focussing on the relationship between television and national imagination. It locates Vietnamese television in the experiences of everyday life and the prevailing network of power relations resulting from marketization and globalization, and, as such, moves beyond the clichéd assumption of Vietnamese media as a mere propagandist instrument of the party state. With examples from a wide range of television genres, the book demonstrates how Vietnamese television enables novel conditions of cultural oppression as well as political engagement in the name of the nation. In sharp contrast to the previous image of Vietnam as a war-torn land, post-Reform television conjures into being a new sense of national belonging based on an implicit rejection of the socialist past, hopes for peace and prosperity, and anxieties about a globalized future. This book highlights the richness of Vietnam’s current culture and identity, characterized, the book argues, by ‘fraternity without uniformity’.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Australie (lieu de production du savoir); Vietnam (corpus analysé); _Nettoyé

New Television, Globalisation, and the East Asian Cultural Imagination - Keane, Michael; Fung, Anthony Y. H.; Moran, Albert (Hong Kong University Press, 2007)
This volume is divided into three parts: 'Adaptation and Local Production in East Asia', 'Formats, Clones, and Generic Variations' and 'New Television'.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Chine (corpus analysé); Corée du Sud (corpus analysé); Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); Japon (corpus analysé); Taiwan (corpus analysé); _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé